Analysis of factors affecting employee productivity - Suryani, Suryani; Fitri, Marliza Ade (Journal of Management and Business Insight, 2023)
Purpose-Internal and external factors can affect employee productivity. This study examined the relationship between occupational health, safety, and work environment, which is thought to affect employee productivity. Design/Methodology/Approach-The study population focused on the employees of the Semen Merah Putih Branch Company. The research data was collected through questionnaires administered to all employees, totaling 47 respondents. The research data were then processed using SPSS. Findings-Occupational health, safety, and working conditions all had a favorable impact on employee productivity. That is, when workplace support systems and occupational health and safety policies are implemented as effectively as possible, productivity at work will rise, thereby enhancing company performance. Research limitations/implications-Every business actor needs to focus on optimizing occupational health and safety to encourage increased employee productivity. To support this, business actors must also pay attention to other factors, such as creating a comfortable and safe work environment, to maximize efforts to achieve employee productivity. Originality/value-Currently, there is a dearth of research on employee productivity, especially for companies engaged in the industry. Previous studies of employee productivity have examined the internal and external aspects of employees, such as motivation, leadership, and organizational culture.